Avaliação da fratura por torção de instrumentos de NiTi tratados e não tratados termicamente - Giraldes, Janaina Folly Nunes (2017)
The objective of this study was to compare the resistance to fracture by torsion of the nickel titanium (NiTi) instruments without and with heat treatment in re-ciprocating movement. Twenty NiTi instruments were selected (n=20): ten ProDesing R instruments with thermal treatment and ten ProDesing R instruments without treat-ment, all 25 mm long, tip size ISO 25 and taper 0.06. After the selection of the samples, the instruments were tested on a TT100, applying a torque load until the moment of the fracture with the function of measuring the maximum final force of the angle of rotation of the instruments. The instruments were measured with a digital caliper ( Mi-tutoyo Digimatic Caliper). The instruments were measured with a digital caliper 3mm from its tip (Do) and fixed to this measure to a mandrel connected to the load cell of the equipment and its rod fixed in a mandrel on the opposite side of the tip and were rotated in a counterclockwise direction, a speed of 3rpm until fracture. The torque load (Ncm) and the angular rotation (o) were monitored and recorded in software analysis TT100 (Odeme Dental Research, Luzerna, Brasil) until the moment of the fracture. Statistical data were performed using parametric methods (test t. de Student). The results showed that the maximum torsional force up to the fracture of the PR instru-ments was lower than the PRNT instruments (P<0.05). The PR instruments presented a greater angular rotation until the fracture when compared to PRNT(P<0.05). The scanning electron microscopy of the fracture surface showed similar torsional fracture characteristics for the two instruments tested, such as concentric abrasion marks and fibrous undulations in the center of rotation. It is concluded that the heat treatment of nickel titanium (NiTi).